Wanderungszentralität und Wanderungsfolgen in Japan - Schöller, Peter (ERDKUNDE, 1973)
Against the expectation of leading demographers, the results of the 1970 Census confirmed the unbroken strength of internal migration in Japan. Since the growth of the millionaire cities is increasingly shifting into the areas beyond their administrative boundaries, evaluation of this phenomenon must be carried out in spatial terms. An analysis of out-migration of miners and retail traders from the Hokkaido mining town of Ishikari-Numata, struck by pit closures, shows the consequences and problems of those peripheral areas in Japan which are being affected by strong out-migration. At the same time it demonstrates the growing migration pull of places with high centrality, especially the prefecture town of Sapporo. Figures 2 and 3 show the concentration of growth in the leading prefecture towns which is also felt in other regions of Japan. Growth-Rank and Primacy yield a picture of the clear strengthening of existing centralisation. This is primarily controlled by the multifunctional multiplicity of opportunities offered by the economic structure, good secondary and further education ooportunities and the higher inner-urban recreational amenity of modern big-city life. The threshold for increasing self-reinforcement can be estimated, under current conditions of Japanese urban and industrial society, to be an urban population of 300,00.